1993
DOI: 10.1007/bf01976172
|View full text |Cite
|
Sign up to set email alerts
|

Stable transformation of peanut callus viaAgrobacterium-mediated DNA transfer

Abstract: Transformed callus was produced from peanut (Arachis hypogaea L. cv. Okrun) hypocotyl explants after four days of co-cultivation with Agrobacterium tumefaciens strains EHA101, LBA4404 or ASE1 carrying the binary vector pKYLX71GUS on a defined medium followed by selection with kanamycin (200 mg 1-1). Transformed calluses were cultured as independent cell lines potentially derived from a single transformation event. Stable integration and expression of foreign gene(s) in the callus was confirmed by Southern and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Among them, octopine and nopaline have been used to achieve higher transformation efficiency. Comparative study of nopaline (C58/LBA4404) and agropine (EHA101) strains showed higher gene transformation efficiency with EHA101 under defined culture conditions (Egnin et al ., ; Franklin et al ., ). Although Agrobacterium biotypes have been tested individually for the transformation studies in peanut, extensive comparative studies are lacking with different strains comprising a single binary vector in a highly potent genotype.…”
Section: Genetic Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, octopine and nopaline have been used to achieve higher transformation efficiency. Comparative study of nopaline (C58/LBA4404) and agropine (EHA101) strains showed higher gene transformation efficiency with EHA101 under defined culture conditions (Egnin et al ., ; Franklin et al ., ). Although Agrobacterium biotypes have been tested individually for the transformation studies in peanut, extensive comparative studies are lacking with different strains comprising a single binary vector in a highly potent genotype.…”
Section: Genetic Transformationmentioning
confidence: 99%
“…The virus remains infective in buffered plant extracts after dilution to 10 −3 , 3‐day storage at 20 °C and heating for 10 min only at 60 °C. In view of lack of resistance sources in peanut germplasm, preliminary attempts were made to develop transgenic plants using PStV coat protein gene (Franklin et al ., ). Later, successful attempts were made to develop transgenic plants carrying two coat protein genes untranslatable full‐length sequence ( CP2 ) and translatable CP gene with an N‐terminal truncation ( CP4 ) of PStV, which offered resistance to viral inoculation under glasshouse conditions.…”
Section: Biotic Stressesmentioning
confidence: 99%
“…Wild-type Agrobacterium strains, nopaline-type C58 and agropine-type A281 77, are considered as virulent for large-seed legumes, including pea (Puonti-Kaerlas et al 1989; De Kathen and Jacobsen 1990) or peanut (Franklin et al 1993;Mansur et al 1993). The octopine-type strain Ach5 was used on a limited scale in transformation experiments on this group of legumes.…”
Section: Transformation Of Yellow Lupin By Using Agrobacterium Tumefamentioning
confidence: 99%
“…Early efforts to transform bean demonstrated its susceptibility to Agrobacterium, and some transgenic tissues, such as callus, leaves, meristems, cotyledon and hypocotyl , have been achieved (Lippincott et al, 1968;McClean et al, 1991;Franklin et al, 1993;Becker et al, 1994;Lewis and Bliss, 1994;Brasileiro et al ., 1996;Nagl et al ., 1997). Mariotti et al (1989) reported the production of transgenic bean plants through the utilization of the Agrobacterium system.…”
Section: Gene Transfer To Phaseolus Vulgarismentioning
confidence: 99%
“…Embryogenic callus (Ozias-A kins et al, 1993;Livingstone and Birch, 1997), zygotic embryos ( Schnall and Weissinger, 1993) and embryonic leaflets ( Livingstone and Birch, 1995) have been used for transfo rmation using particle gun bombardment in peanut. Dong et al, 1990Lacor te et al, 1991Mansur et al, 1993Franklin et al, 1993Mc Kently et 01., 1995 Freitas et 01., 1997 Eapen and Geo rge, 1994Cheng et al, 1994Sharma et al, 1993Ping et al, 1996Cheng et al, 1997Egnin et al, 1998Khandelwal et al, 1999Venkataehalam et al, 1998b Rohini and Shankara, Rao 2000 Jarret and Demski, 1997 Sharma and Anjaia h, 2000 Among the different genes that have been introduced by particle gun bombardment are 2S albumin gene from Brazil nut (Lacorte et al, 1997), crylAc gene from Bacillus thuringensis (Sing sit et al, 1997) and nucleocapsid protein gene of tomato spotted wilt virus (Yang et al,I998a), improved nutritional protein gene (Lewis et al, 1998) and synthetic antifungal peptide gene (Yang et al ., 1998b). Dong et al, 1990Lacor te et al, 1991Mansur et al, 1993Franklin et al, 1993Mc Kently et 01., 1995 Freitas et 01., 1997 Eapen and Geo rge, 1994Cheng et al, 1994Sharma et al, 1993Ping et al, 1996Cheng et al, 1997Egnin et al, 1998Khandelwal et al, 1999Venkataehalam et al, 1998b Rohini and Shankara, Rao 2000 Jarret and Demski, 1997 Sharma and Anjaia...…”
Section: Dir Ect Dna Tr Ans Fer Usin G Particl E Gun Bomb Ardm Entmentioning
confidence: 99%